Memorial educação no campo: reflexões de uma professora do município de Anapu - SOUSA, Camila Silva e (2023)
This research in the form of an academic memorial will address rural education, through real reports about my life story. My objective is to propose a reflection on the difficulties experienced by people who live in the rural area of the municipality of Anapu; to analyze the factors that involve education and that interfere in the learning and permanence of the peasant student, to verify the process and the selection criteria of the educators that work in the rural region of the municipality of Anapu. Reflect on the Pedagogical practices of teachers who work in the rural region of the municipality of Anapu. The research is justified by bringing elements of the reality of the people of the rural area of this municipality, since it is extremely important to reflect on the education offered to the peasant people, which often does not take into account the complexity of factors that involve life rural students who need to work to help support their families. To theoretically base this work through Freire (1987) and Hage and Barros (2010). In the development of this study I chose to divide it into four parts. The opening part of this memorial will be a personal narrative reminiscing from my childhood. In the second part I will describe how I had the first contacts with the school and the beginning of my profession. Finally, I will narrate about PARFOR. In the final considerations I will reflect on the findings.